ERA-CRISPR/Cas12a-based, fast and specific diagnostic detection for Chlamydia pneumoniae - Zhou, Yanxia; Yan, Zijun; Zhou, Shi; Li, Weiwei; Yang, Hongyu; Chen, Hongliang; Deng, Zhongliang; Zeng, Qilin; Sun, Peiyuan; Wu, Yimou (Frontiers in Cellular and Infection Microbiology, 2024)
Chlamydia pneumoniae (C. pneumoniae) is a specialized intracellular parasitic pathogen capable of causing pneumonia, sinusitis, bronchitis, and other respiratory diseases, which pose significant public health challenges. Therefore, rapid, accurate, and sensitive diagnosis is crucial for the prevention and treatment of respiratory diseases caused by C. pneumoniae. In this study, we combined enzymatic recombination amplification (ERA) with the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein (Cas) 12a system (CRISPR/Cas12a) to develop a dual detection platform termed the Cpn-ERA-CRISPR/Cas12a dual system. This system integrates both the ERA-CRISPR/Cas12a fluorescence system and the ERA-CRISPR/Cas12a lateral flow system. Detection results can be measured using a fluorescence detector or observed with the naked eye on lateral flow strips. The fluorescence system and the lateral flow system detect C. pneumoniae in 30 minutes and 15 minutes, respectively. This dual system exhibits no cross-reactivity with the other seven pathogens, demonstrating high specificity, and achieves a sensitivity of 100 copies/µL. Additionally, the Cpn-ERA-CRISPR/Cas12a dual system was employed to analyze 39 clinical samples, comprising 19 positive and 20 negative samples. The detection rate for positive samples was 100%, with no positive results in the negative samples, indicating a high level of concordance with qPCR results. In summary, the Cpn-ERA-CRISPR/Cas12a dual system represents a novel tool for diagnosing C. pneumoniae and holds promising application potential in grassroots community hospitals.